From Parity Violation to Hadronic Structure and more Proceedings of the 3rd International Workshop Held at Milos, Greece, May 16-20, 2006 - Jager, K. de.; Kox, S.; Lhuillier, David; Maas, Frank; Page, S.; Papanicolas, C.; Stiliaris, S.; Wiele, J. Van de.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
c Societ` a Italiana di Fisica / Springer-Verlag 2007 The third workshopFrom Parity Violation to Hadronic Structure and more ... was held from May 16 to May 20, 2006, at the George Eliopoulos conference center on the Greek island of Milos. It is part of a series that started in Mainz in 2002 and was followed by a second workshop in Grenoble in 2004. While originally initiated by the extraction of the strangeness contribution to the electromagnetic form factors of the nucleon, we have continuously broadened the focus of this workshop series to the application of parity violation usinghadronicprobesandtoparityviolation experimentsinatomicphysics.Meanwhiletherehavebeenmanyexciting new proposals for using parity violation in other areas like in the search for new physics beyond the standard model or in exploring hadron structure. There are also close connections to the open question on the size of the two-photon exchange amplitude. Fifty years after the 1956 proposal of Lee and Yang to test the hypothesis of violation of parity symmetry in the weak interaction, the many applications of parity violation in very di?erent experiments are way beyond the scope of what Lee and Yang could have imagined. For the physics topics discussed during this workshop, the application of parity violation has become a standard workhorse that allows to extract many physics topics in di?erent experiments.
Hadron structure on the lattice and in the continuum -- Future directions in parity violation -- Strangeness in the Nucleon and Related Topics: Theory -- Quark model analysis of strangeness form factors of the proton -- Strange nucleon form factors: Solitonic approach to G M s , G E s , and and comparison with world data -- Implications of the JLab proton polarization data for the behavior of strange nucleon form factors -- Flavor content of nucleon form factors in a VMD approach -- Isospin breaking in the vector current of the nucleon -- Interpretation of the NuTeV experiment -- Nucleon form factors and dispersion relations -- Nucleon form factors of the isovector axial-vector current -- The controversial role of strangeness in the spin structure of the nucleon -- Strangeness contributions to nucleon form factors -- Probing nucleon structure on the lattice -- Strangeness in the Nucleon and Related Topics: Experiment -- New results from the HAPPEX Experiments at Q2 = 0.1 GeV/c2 -- The parity violation A4 experiment at forward and backward angles -- Results from the forward G0 experiment -- The G0 backangle measurements -- Kinematics and backgrounds for HAPPEX measurements -- Nucleon form factors and the BLAST experiment -- Determination of the gluon polarization at RHIC and COMPASS -- A Monte-Carlo method to analyze the electromagnetic form factors of the nucleon -- Two-Photon Exchange -- Beam normal spin asymmetries: Theory -- Transverse single spin asymmetry at the A4 experiment -- Transverse beam asymmetries measured from 4He and hydrogen targets -- Parity Violation with Hadronic Probes -- Overview of hadronic parity violation -- Parity violation in neutron spin rotation -- Two-pion-exchange parity-violating potential and np ? d? -- Parity Violation in Atomic Physics -- Theoretical overview of atomic parity violation -- Pump-probe measurement of atomic parity violation in cesium with a precision of 2.6% -- Program of parity nonconservation measurements in francium -- Towards measuring nuclear-spin-dependent and isotopic-chain atomic parity violation in ytterbium -- Prospects for parity violation measurements in cold francium atoms -- New Projects using Parity Violation: Search for New Physics -- Electroweak physics at LHC -- The E158 experiment -- The Q weak p experiment at Jefferson Laboratory -- Outlook for an improved measurement of parity violation in Moeller scattering at Jefferson Laboratory -- Parity violation and the nature of charges -- Parity-violating DIS at 12 GeV -- Measuring sin2 ? W with parity violation in deep inelastic scattering with baseline spectrometers at JLab 12 GeV -- New Projects using Parity Violation: Probing Hadronic Systems -- Parity violation in deep inelastic scattering at JLab 6 GeV -- Res-Parity: Parity violation in inelastic scattering at low Q2 -- Parity violation, the neutron radius of lead, and neutron stars -- The lead radius experiment PREX -- Technical Developments for Parity Violation Experiments -- Helicity correlated asymmetries caused by optical imperfections -- Controlling helicity-correlated beam asymmetries in a polarized electron source -- Laser Compton polarimetry at JLab and MAMI -- New methods for precision Møller polarimetry -- Rearrangement of the A4 calorimeter for the backward angle measurement -- The optical system of the A4 laser Compton polarimeter -- Workshop Summary -- Conclusions and perspectives.
Keywords: Nuclear physics; Heavy ions; Elementary particles (Physics).; Quantum field theory; Nuclear Physics, Heavy Ions, Hadrons; Elementary Particles, Quantum Field Theory